The Influence of Board of Commissioners Size, Company Size, and Profitability on Corporate Social Responsibility (CSR) Disclosures (Study on Pharmaceutical Companies Listed on the Indonesia Stock Exchange 2016-2019) - Ridho Dwiki Dharmawan; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of Board of Commissioners Size, Company Size, and Profitability on Corporate Social Responsibility (CSR) Disclosures (Study on Pharmaceutical Companies Listed on the Indonesia Stock Exchange 2016-2019). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 8 Pharmaceutical Companies Listed on the IDX for the 2016-2019 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that the size of the Board of Commissioners has an effect on Corporate Social Responsibility in pharmaceutical companies listed on the IDX for the 2016-2019 period. Company size has an effect on Corporate Social Responsibility in pharmaceutical companies listed on the IDX for the 2016-2019 period. Profitability has an effect on Corporate Social Responsibility in pharmaceutical companies listed on the IDX for the 2016-2019 period.